Review of the genus Susuacanga (Coleoptera, Cerambycidae, Cerambycinae) - Botero R., Juan Pablo (Zootaxa, 2014)
The genus Susuacanga Martins, 1997 is redescribed. A new combination, S. blancaneaui (Bates, 1880) comb. nov. and a new synonymy, Eburia unicolor Bates, 1870 = S. octoguttata (Germar, 1821) are proposed. The genus is now composed of 12 species. The geographical distribution of S. opaca is expanded to include Belize. Photographs of Susuacanga species are included and a key to differentiate them is provided.